Palaeoclimatic and hydrological environments inferred by moisture indexes from the S4 palaeosol section in the Xi'an region, China. (10th November 2018) - Zhao, Jing-Bo; Ma, Yan-Dong; Lui, Rui; Luo, Xiao-Qing; Shao, Tian-Jie
Abstract: We used indexes of soil moisture content to reconstruct water balance and vegetation type during the development of the palaeosol S4 of the loess-palaeosol sequence in the Xi'an area of China. Goethite–Fe-Mn concretions were found within S4 from field survey and laboratory analyses, and their presence is used as an indicator of soil moisture content and the depth distribution of groundwater. From a comparison of the goethite–Fe-Mn concretions, weathered-leached loess layer, and the vertical migration distance of CaCO3 between various sections in the Xi'an region, we infer a subtropical climate with annual average temperature 15–16 °C and annual average precipitation of 900–1000 mm during the development of S4 . At that time, unlike today, the Qinling Mountains were not the boundary between subtropical and temperate climatic regions. Our results show that the depth distribution of soil gravitational water in the Xi'an region reached 3.3 m; the average soil moisture content within the 0–3.3 m depth range was ∼25%, after water consumption by evapotranspiration; and the soil moisture content within the goethite–Fe-Mn concretion layer was close to saturation, at ∼48%. Soil moisture was abundant and the water balance was positive and a large amount of moisture was supplied to the groundwater each year, which was conducive for the development of forest vegetation.